Implementation of Legal Protection for Women with Disabilities Victims of Rape Crime in Langkat District - Rizky Ayu Sugiani (Journal of Law Science, 2023)
Women with disabilities are weak creatures and have deficiencies in themselves. Women with disabilities are vulnerable to becoming victims of criminal acts, especially women who are vulnerable as victims of rape. Especially women with disabilities in the city of Langkat. Women with disabilities are victims of the crime of rape, so they need a legal protection that is provided based on relevant laws and regulations and already has regulations. It is necessary to provide legal protection, especially legal protection for women with disabilities who are victims of rape in Langkat district. The problem in this writing is in the form of legal regulations, various forms of legal protection provided to women victims of disabilities in Langkat district and prevention that can be taken to reduce the number of criminal acts of rape in Langkat district. The research method used in this journal article is in the form of normative and empirical juridical, analytical description and data collection which is taken through library research and file research.